A multi-objective approach for micro grid energy management based on fuzzy multi-agent decision-making process. (2016) - Serraji, Maria; Nfaoui, El Habib; Boumhidi, Jaouad
In this paper, we present an improved fuzzy multi-agent decision-making process for micro grid energy management considering uncertainty and imprecision associated with renewable energy sources, electricity market price and load. This approach is proposed to solve a decision-making problem that implies economical/technical objectives which operates under different constraints. The main idea of this approach is promoting the agent global decision impact on the local decision made by each agent independently and separately for efficient power resources management operation. For this, a coordinator agent seeks to satisfy assigned objectives based on local decisions generated by fuzzy logic inference, using an indicative number to differentiate the priority of producing energy between units in order to support the final decision about the power that should be generated by each agent. Simulation results show that the proposed method is beneficial to handle the problem of MG energy management in flexible manner.